IMPLEMENTASI PERATURAN DAERAH KABUPATEN BANYUMAS NOMOR 6 TAHUN 2019 TENTANG RENCANA DETAIL TATA RUANG KAWASAN PERKOTAAN PURWOKERTO - Paulus Israwan Setyoko (Jurnal Administrasi Negara, 2022)
This study seeks to investigate in further detail the Implementation of Banyumas Regency Regulation No. 6 of 2019 on the Detailed Spatial Planning of the Purwokerto Urban Area. This study was cunducted in Banyumas Regency utilizing qualitative method with a case study approach. This study found that in the idealized policy aspect, spatial planning policies is used to regulate space utilization, spatial and environmental planning, and that includes fundamental materials for example program provisions related to buildings and the environment as a guide for the design of buildings in a region. Next in the aspect of target group, the implementation of spatial planning policies tries to engage all stakeholders through deliberative forums and public hearings. Moreover, in the implementing organization aspect, it demonstrates that the parties involved in the implementation of urban spatial planning policies are the local government of Banyumas Regency, Banyumas Regional People's Representative Council, the community, the private sector, the head of sub-district, the head of village. Lastly, in the environmental factor aspect, it was identified that the Purwekerto regency’s urban spatial planning policies was successfully implemented in terms of the social environment and the bureaucracy environment.